2001
DOI: 10.1074/jbc.m107574200
|View full text |Cite
|
Sign up to set email alerts
|

αv Integrin, p38 Mitogen-activated Protein Kinase, and Urokinase Plasminogen Activator Are Functionally Linked in Invasive Breast Cancer Cells

Abstract: We reported previously that endogenous p38 MAPK activity is elevated in invasive breast cancer cells and that constitutive p38 MAPK activity is important for overproduction of uPA in these cells (Huang, S., New, L., Pan, Z., Han, J., and Nemerow, G. R. (2000) J. Biol. Chem. 275, 12266 -12272). However, it is unclear how elevated endogenous p38 MAPK activity is maintained in invasive breast cancer cells. In the present study, we found that blocking ␣ v integrin functionality with a functionblocking monoclonal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
46
1

Year Published

2002
2002
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 59 publications
9
46
1
Order By: Relevance
“…It was reported by Sitrin et al that integrins and uPAR are associated via carbohydrate-lectin interaction and that this physical association is necessary for collaboration (23). Recent studies have shown that integrins can activate the p38 MAPK pathway and that · v integrin, p38 MAPK and uPA are functionally linked in breast cancer cells (14). These earlier observations prompted us to investigate whether the p38 MAPK pathway is important for breast cancer cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported by Sitrin et al that integrins and uPAR are associated via carbohydrate-lectin interaction and that this physical association is necessary for collaboration (23). Recent studies have shown that integrins can activate the p38 MAPK pathway and that · v integrin, p38 MAPK and uPA are functionally linked in breast cancer cells (14). These earlier observations prompted us to investigate whether the p38 MAPK pathway is important for breast cancer cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Since uPAR lacks transmembrane and intracytoplasmic domain for uPA-induced signal tranduction, uPAR-integrin collaboration is essential. It was demonstrated that endogenous p38 mitogen-associated protein kinase (MAPK) activity is elevated in cultured breast cancer cells and that increased p38 MAPK activity is essential for breast cancer invasiveness by stabilizing uPA mRNA (14,15). Signal transduction via integrin may induce the MAPK pathway, since recent studies have shown that p38 MAPK modulates the proliferation of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…An integrin receptor strongly involved in angiogenesis and tumor growth is ␣ v ␤ 3 -integrin [67][68][69]. This integrin can bind vitronectin and fibronectin and various other proteins with an arginine-glycine-aspartic acid (RGD) (Arg-Gly-Asp) sequence, like fibrinogen, von Willebrand factor and denatured collagen [62,66].…”
Section: Cell-matrix Interactionmentioning
confidence: 99%
“…This integrin can bind vitronectin and fibronectin and various other proteins with an arginine-glycine-aspartic acid (RGD) (Arg-Gly-Asp) sequence, like fibrinogen, von Willebrand factor and denatured collagen [62,66]. Different reports have correlated expression of integrins with more invasive phenotypes of tumor cells and activation of MT1-MMP and MMP-2 [67,[69][70][71]. An explanation for the activation of MMP-2 is its capacity to bind ␣ v ␤ 3 -integrin through its fibronectin like repeats.…”
Section: Cell-matrix Interactionmentioning
confidence: 99%
“…Although two later case -control studies did not confirm an increased risk of invasive breast cancer among Leu33Pro homozygotes (Ayala et al, 2003;Jin et al, 2004), certain considerations nevertheless favour the possibility that the ITGB3 Leu33Pro polymorphism may influence risk of invasive breast cancer. First, beta 3 integrins are ectopically expressed on breast carcinoma cells where they enhance invasive and metastasiogenic properties of these cells (Murthy et al, 1996;Wewer et al, 1997;Chen et al, 2001Chen et al, , 2004Rolli et al, 2003). Second, the Pro33 vs Leu33 allele enhances integrin-mediated activation of MAPK pathways (Vijayan et al, 2003), crucial for the malignant potential of cancer cells (Johnson and Lapadat, 2002).…”
mentioning
confidence: 99%